Evaluation of coronavirus in tears and conjunctival secretions of patients with SARS‐CoV‐2 infection. Issue 6 (12th March 2020) - Xia, Jianhua; Tong, Jianping; Liu, Mengyun; Shen, Ye; Guo, Dongyu
Abstract: Objective: This study aimed to assess the presence of novel coronavirus in tears and conjunctival secretions of SARS–CoV‐2‐infected patients. Methods: A prospective interventional case series study was performed, and 30 confirmed novel coronavirus pneumonia (NCP) patients were selected at the First Affiliated Hospital of Zhejiang University from 26 January 2020 to 9 February 2020. At an interval of 2 to 3 days, tear and conjunctival secretions were collected twice with disposable sampling swabs for reverse‐transcription polymerase chain reaction (RT‐PCR) assay. Results: Twenty‐one common‐type and nine severe‐type NCP patients were enrolled. Two samples of tear and conjunctival secretions were obtained from the only one patient with conjunctivitis yielded positive RT‐PCR results. Fifty‐eight samples from other patents were all negative. Conclusion: We speculate that SARS‐CoV‐2 may be detected in the tears and conjunctival secretions in NCP patients with conjunctivitis. Highlights: SARS‐CoV‐2 may be detected in the tears and conjunctival secretions in NCP patients with conjunctivitis. SARS‐CoV‐2 was not detected in the conjunctival sac of NCP patients without conjunctivitis. The possibility of eye infection and the ocular route as a potential infection source should be considered and further examined, and scientific protection should be carried out.